A roda de conversa na educação infantil: análise de seus aspectos formativos com crianças de três a cinco anos - Bertonceli , Marcia (2016)
The language occupies a prominent place in the humanization of the subject, by propelling aspects of specific and constitutive human consciousness development, and the organization of higher psychic processes through verbal interactions. The Conversation Wheels are language activities permanently in early childhood education, in order to develop oral communication, expression and child interaction. Based on these assumptions, this study aimed to analyze the formative aspects of educational practices with verbal language, the conversation wheels made with a group of children from three to five years, in three public institutions of Early Childhood Education in the municipality of Francisco Beltrao in 2014. qualitative and ethnographic, was developed through literature reading area, highlighting works that provided current and relevant data on the subject; analysis of curriculum documents; audio recordings twenty-four Conversation wheels and semi-structured interviews with three teachers of the institutions of the research context. Based on dialogue between studies on childhood, historical-cultural psychology, Vygotsky and the dialogic perspective of language, Bakhtin, established reflections on the child's possibilities of expression and on the way children's voices are in the educational process Talk wheel, our research object. Ressaltamos The basic concept of verbal interaction, by which they give cultural appropriation, and constitutivity of language as humanization conditions and key elements in Early Childhood Education, linked to the importance of listening to the children to develop their linguistic expression. From the study of the theoretical and methodological framework, the guiding curricular work documents on EI and the data produced in the survey, identify the categories of analysis - (I) the cultural content in the movement of the wheel, (II) the verbal interactions drive the wheel: dialogism and polyphony and (III) formative elements of RC - with which we analyze the Talk Wheels and highlight its educational potential as a space that promotes dialogue, values the children's uniqueness, calls the dialogue between everyday knowledge and the know scientific, allows the construction of values, cultural knowledge and the democratization of knowledge. Within the limit of determinations and contradictions of historical contexts, their practice points to the challenge of breaking with guidelines characterized by possibility of rigidity of teaching practices; It points to the need for restoration of the dialogue with a view to bring children's voices to the movement, allowing the meeting of dissonant voices in the wheel and consider the integral formation of children.